Safety and security practices among hotels in Terengganu: perspectives from hotel managers / Jazira Anuar - Anuar, Jazira; Musa, Mushaireen; Khalid, Khazainah; Abu Bakar, Siti Khuzaimah (2019)
Safety and security practices are essential in the hotel and tourism industries for centuries. With the extreme competition among hotels to accomplish guests demand patterns, hoteliers has configure their hotel’s safety and security systems to deliver exemplary hospitality. Limited study has highlighted issues with regards to hotel safety and security systems especially from operators/ manager’s point of views. Thus, the objective of this research paper is to explore perceptions of hotel safety and security managers’ on the relative importance of safety and security facilities. In-depth interviews with eight (8) hotel managers and assistant managers of Security Department were entrenched. They came various hotels in Kuala Terengganu, however the hotel’s names were not revealed for anonymity purposes. Four (4) themes were derived from the interview that consists of employee’s safety and security training; need for female guest floors, well-equipped fire prevention systems and closed-circuit television system (CCTV). The findings also discovered that managers perceived uniformed security guard, emergency lighting systems and access of guest key to activate the lifts to guest floors as essential element in hotel safety. This finding served as a platform to assist hotel managers in comprehends their guest needs. This can also lead to customer satisfaction and image reputation. The managerial implications, recommendations and scope for future study are presented in the end.